Speech of Hon. Kenneth Rayner, in the convention of 1835 - Rayner, Kenneth, 1808-1884 (Executive Committee of the Wake County Democratic Club, 1855)
Speech by Hon. Kenneth Raynor, delivered at the Convention of 1835, and republished in 1855. In this address he advocated for religious liberty with respect to membership into the General Assembly, which did not allow Catholics or Jews. Also attached were two 1855 letters which discussed the "Know-Nothing" party and the authors' objection to its philosophy and beliefs.